Affiliated mutual funds and the allocation of initial public offerings - Ritter, Jay R.; Zhang, Donghang (Journal of Financial Economics, 2007)
We examine how investment banks use initial public offerings (IPOs) in relation to their affiliated mutual funds. The dumping ground hypothesis predicts that the lead underwriter allocates cold IPOs to its affiliated funds so that more deals can be completed when demand for these IPOs is weak. Affiliated funds could also receive more cold IPOs because the lead underwriter uses allocations of hot IPOs to unaffiliated funds to gain trading commission business. The nepotism hypothesis predicts that the lead underwriter allocates hot IPOs to its affiliated funds to boost their performance and thus attract more money. We find little evidence supporting the dumping ground hypothesis, although some evidence supports the nepotism hypothesis, especially during the internet bubble period of 1999–2000.